ANALISIS ASUHAN KEPERAWATAN PADA PENDERITA DIABETES MELITUS DENGAN PENERAPAN INTERVENSI SENAM KAKI DIABETIK UNTUK MERINGANKAN GEJALA NEURO PATI DIABETIK - Nanda Syifa Melinda (2023)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to abnormalities in the insulin system. If diabetes mellitus is left without proper treatment, it can cause several complications, including retinopathy, neuropathy, or neuropathy. Disruption of nerve structure and function that occurs in diabetic neuropathy causes the patient to experience tingling, numbness, a feeling of stabbing or burning pain, and decreased sensitivity in the patient's feet. One of the treatments for diabetic neuropathy to improve blood flow and increase the sensitivity of the feet is diabetic foot exercise therapy. This study discusses the effect of diabetic foot exercise on people with diabetes mellitus with neuropathy using nursing care methods. The results of this study prove that there is an effect of diabetic foot exercise in alleviating the symptoms of diabetic neuropathy as evidenced by a decrease in the pain scale from a scale of 6 to a scale of 3, reduced tingling that is felt, improved CRT results from >3 seconds to <2 seconds, increased foot sensitivity, as well as smoothing blood flow which is characterized by warm acral and does not look pale.